Organizing Networks: An Actor-Network Theory of Organizations - Belliger, Andréa; Krieger, David J. (transcript, 2016)
What are organizations? Where do they come from? How are they transformed and adapted to new situations? In the digital age and in the global network society, traditional theories of the organization can no longer answer these questions. Based on actor-network theory, this book explains organizations as flexible, open networks in which both human and non-human actors enter into socio-technical assemblies by constantly negotiating and re-negotiating programs of action. Organizations are not macro social structures or autonomous systems operating behind the backs of individuals. Instead, they are scalable actor-networks guided by network norms of connectivity, flow, communication, participation, authenticity, and flexibility.